2010
DOI: 10.1007/s12288-010-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Myeloid Leukemia Presenting with Visual and Auditory Impairment in an Adolescent: An Insight to Management Strategies

Abstract: A 15-year-old girl presented with progressive deterioration in vision and hearing over 1 week. A huge spleen was palpated below the left costal margin laying down to inguinal region. Blood count showed hyperleukocytosis with a white blood cell count of 455 × 10(9)/l. Peripheral smear yielded myeloid precursor cells with basophilia. Bone marrow aspiration revealed a blast count of 5% morphologically and 4% by flow cytometry. Fundoscopic examination revealed bilateral retinal exudates, edema and hemorhages. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…Similar to our observation, previous case reports have also demonstrated that various interventions like hydroxycarbamide, low dose cytarabine, dexamethasone, intrathecal methotrexate, intra tympanic steroids have been unsuccessful in reversing the hearing loss [10,17]. Two reports have shown a beneficial role of leukapheresis [9,16], while others have not [17,[25][26][27]. Thus, current literature shows irreversibility of SNHL in the majority of the cases [10,17], highlighting that an irreparable damage to the inner ear or auditory area in the brain occurs rapidly, and an early diagnosis and aggressive cytoreductive intervention is warranted.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to our observation, previous case reports have also demonstrated that various interventions like hydroxycarbamide, low dose cytarabine, dexamethasone, intrathecal methotrexate, intra tympanic steroids have been unsuccessful in reversing the hearing loss [10,17]. Two reports have shown a beneficial role of leukapheresis [9,16], while others have not [17,[25][26][27]. Thus, current literature shows irreversibility of SNHL in the majority of the cases [10,17], highlighting that an irreparable damage to the inner ear or auditory area in the brain occurs rapidly, and an early diagnosis and aggressive cytoreductive intervention is warranted.…”
Section: Discussionsupporting
confidence: 88%
“…Visual or hearing loss are rare clinical manifestations of CML with 29 cases reported [7,[9][10][11][12][13][14][15][16][17]. Deafness as the presenting symptom is even rarer in CML-CP, with bilateral moderate-profound SNHL seen in all our patients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although few, cases of deafness in patients with CML secondary to hyperleukocytosis/leukostasis have been reported [ 2 – 4 ]. Early cytoreduction with leukopheresis and/or chemotherapy led to reversal of symptoms in some patients [ 5 7 ]. However, small leukocytic thrombi secondary to hyperleukocytosis can cause occlusion of blood vessels and their small branches causing infarction and permanent end organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, under pathological conditions such as leukostasis circulating leukocytes can form aggregates, obstruct small vessels in organs, and eventually lead to serious problems like convulsion, stroke, visual, and auditory impairment. [15][16][17] Evidently, a precise knowledge of the adhesion characteristics of these non-adherent cells will be important for our understanding of how such phenomenon takes place as well as for finding possible prevention/ treatment strategies. In addition, although it is widely known that the formation of tight contact regions (often referred to as focal adhesions) between cells and the extracellular matrices (ECMs) requires the assembly of numerous proteins in the intracellular side, 1 very few studies have explored the question of whether and how the appearance of adhesion alters the mechanical response of cells.…”
mentioning
confidence: 99%